Agile local manufacturing of active pharmaceutical ingredients in Africa could improve health security and economic growth - Cloudius Ray Sagandira (Communications Medicine)
After decades of dependence on imported Active Pharmaceutical Ingredients (APIs) and multilateral aid, Africa faces a critical turning point, seeking to assert control over its health and economic future. Here we discuss how agile local API manufacturing offers a strategic solution to enhance health and economic security, transforming Africa’s pharmaceutical landscape for sustainable medicine access.